How elite coaches' experiential knowledge might enhance empirical research on sport performance - A response to commentary - Greenwood, D.; Davids, K.; Renshaw, I. (International Journal of Sports Science and Coaching, 2012)
In our article, we argued that the integration of empirical knowledge of scientific researchers with the experiential knowledge of elite sport coaches and athletes has the potential to enrich understanding of learning and performance in sport. However, in her commentary, Gabrielle Wulf argued that this approach has limitations. Experiential knowledge is not a substitute for rigorous scientific research and should not be considered in isolation. It is gained through rigorous reflective practice and should be used collaboratively with scientific theory to enhance understanding of learning and performance. While it is generally acknowledged that coaches` knowledge is useful in providing new ideas for research studies, and acts as a useful resource when sparse research on a topic of study exists [1], it is proposed that the collaboration of empirical and experiential knowledge sources provides greater potential to extend understanding of sport scientists when compared to mono-disciplinary knowledge considered separately.